Restorative justice in cases of sexual violence: current and future directions in the UK - Gavin, Paul (Contemporary justice review, 2023)
Restorative justice seeks to repair the harm caused by crime by bringing together victims, offenders, and affected parties in a facilitated dialogue. Restorative justice is often viewed negatively in relation to cases of sexual violence, due to fears of revictimization, retraumatization, and power imbalances. This paper provides a critical analysis of current literature on restorative justice as a response to sexual violence. It presents findings from a small study (n = 25) held after a one-day conference on sexual violence and restorative justice. Findings include support for restorative justice in cases of sexual offending being contingent on the process being victim/survivor-led and specialist training being provided for restorative practitioners who deal with such cases.